2018
DOI: 10.1038/s41388-018-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-137 mediates the functional link between c-Myc and EZH2 that regulates cisplatin resistance in ovarian cancer

Abstract: Platinum drugs are used in first-line to treat ovarian cancer, but most of the patients eventually generate resistance after treatment with these drugs. Although both c-Myc and EZH2 have been implicated in regulating cisplatin resistance in ovarian cancer, the interplay between these two regulators is poorly understood. Using RNA sequence analysis (RNA-seq), for the first time we find that miR-137 level is extremely low in cisplatin resistant ovarian cancer cells, correlating with higher levels of c-Myc and EZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 55 publications
4
71
0
Order By: Relevance
“…[31][32][33] Additionally, miR-137 enhanced the chemosensitivity in ovarian cancer and colon cancer. 34,35 In the present study, we rstly validated that SNHG6 directly targeted miR-137 and repressed miR-137 expression. Moreover, miR-137 mediated the regulatory effect of SNHG6 on radiosensitivity in CRC cells.…”
Section: Discussionsupporting
confidence: 65%
“…[31][32][33] Additionally, miR-137 enhanced the chemosensitivity in ovarian cancer and colon cancer. 34,35 In the present study, we rstly validated that SNHG6 directly targeted miR-137 and repressed miR-137 expression. Moreover, miR-137 mediated the regulatory effect of SNHG6 on radiosensitivity in CRC cells.…”
Section: Discussionsupporting
confidence: 65%
“…miR-137 hypermethylation leads to its inhibition in many tumors, such as colorectal cancer, pancreatic cancer, and endometrial cancer [29][30][31] . Functional analysis has indicated that miR-137 can inhibit cell proliferation, cell cycle arrest and apoptosis, cell migration and invasion, and affect chemoresistance [32][33][34][35][36] . For example, miR-137 overexpression sensitized resistant colon cancer cells to oxaliplatin 20 .…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is involved in treatment resistance in multiple cancers. For example, EZH2 epigenetically regulates the FADD/PARP1 axis, leading to TMZ resistance in glioma 33 ; EZH2 activates cellular survival pathways, resulting in resistance to cisplatin 34 ; and H3K27 mediated by EZH2 induces multidrug resistance in small cell lung cancer 35 . In the present study, EZH2 knockdown partially reversed gefitinib resistance, inhibited cell proliferation, and induced apoptosis in PC9/GR cells.…”
Section: Discussionmentioning
confidence: 99%